HUBUNGAN ANTARA KEBIASAAN SARAPAN PAGI, SIKLUS MESTRUASI DAN BEROLAHRAGA DENGAN ANEMIA GIZI BESI PADA REMAJA PUTRI DI WILAYAH KERJA PUSKESMAS KAMPUNG BALI - Sumiati, Sumiati; Hernawan, Andri Dwi; Marlenywati, Marlenywati (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Profile data of Health Department of Pontianak in 2012 indicated that there were 612 anemia cases (59,6) experienced by adolscents girls at work area of Puseksmas Kampung Bali. This number was consuidered as the highest number of anemia cases in Kota Pontianak. This study aimed at finding out the correlation of breakfast habit, menstrual cycle, physical activity, and iron deficiency anemia among adolescence girls at work area of Puskesmas Kampung Bali.Using observational analysis and cross sectional approach, as many as 244 respondents and 139 samples participated in this study.The study revealed that there were correlation of breakfast habit (p= 0,046 dan PR = 1,393), menstrual cycle (p = 0,043 dan PR = 1,340), physical activity (p = 0,048 dan PR = 1,404), and iron deficiency anemia among adolscence girls at work area of Puskesmas Kampung Bali.From the findings, the local health center is encouraged to conduct socialization about the dangers and the prevention of anemia, as well as distribute brochures and leaflet of anemia to the students.Keywords :breakfast habit, menstrual cycle, physical activity, and iron deficiency anemia